A novel design of poly (3, 4-ethylenedioxythiophene):poly (styrenesulfonate)/molybdenum disulfide/poly (3, 4-ethylenedioxythiophene) nanocomposites for fabric micro-supercapacitors with favourable performances. (1st March 2019) - Chen, Yan; Zhu, Xinhua; Yang, Dingyu; Wangyang, Peihua; Zeng, Biao; Sun, Hui
Abstracts: Fabric supercapacitors with mechanical flexible and excellent energy storage capacity attract considerable attention for the potential application in wearable smart electronics. A novel ternary composite electrode and assembled all-solid-state fabric supercapacitors are expected to achieve favorable electrochemical performances. The facile vapor phase polymerization method is employed to fabricate the ternary poly (3, 4-ethylenedioxythiophene):poly (styrenesulfonate)/molybdenum disulfide/poly (3, 4-ethylenedioxythiophene) composite electrodes. The molybdenum disulfide nanograins are incorporated into the conducting polymer matrix which further facilitates the formation of hierarchical porous structures. On account of profitable synergistic effect among three-component materials and porous structure with reinforced electronic/ionic transport, the as-prepared hybrid electrode exhibits a high areal capacitance of 51.01 mF/cm 2 at current density of 0.1 mA/cm 2, as well as long cycling durability with 93.6% capacitance retention after 5000 cycles of galvanostatic charge/discharge tests. Furthermore, symmetric fabric micro-supercapacitor assembled by the as-prepared electrodes is also evaluated in a belt-shaped device. This assembled device exhibits an energy density of 0.2 μWh/cm 2 (1.81 mWh/cm 3 ) and the power density of 0.09 mW/cm 2 (0.82 W/cm 3 ). These results of excellent flexibility and favourable capacitive performance indicate a promising application in portable and wearable electronic devices. Graphical abstract: Highlights: The highlights of our original work are: Ternary PEDOT:PSS/MoS2 /PEDOT film exhibits excellent electrochemical performances. The superior performance is a result of the synergistic effect of three components. This ternary composite can be simply coated onto flexible textile substrate. This flexible fabric electrode based micro-device is suitable for wearable device.